Altering Trehalose-6-Phosphate Content in Transgenic Potato Tubers Affects Tuber Growth and Alters Responsiveness to Hormones during Sprouting - Debast, Stefan; Nunes-Nesi, Adriano; Hajirezaei, Mohammad R.; Hofmann, Jörg; Sonnewald, Uwe; Fernie, Alisdair R.; Börnke, Frederik (Plant Physiology, 2011)
Trehalose-6-phosphate (T6P) is a signaling metabolite that regulates carbon metabolism, developmental processes, and growth in plants. In Arabidopsis (Arabidopsis thaliana), T6P signaling is, at least in part, mediated through inhibition of the SNF1-related protein kinase SnRK1. To investigate the role of T6P signaling in a heterotrophic, starch-accumulating storage organ, transgenic potato (Solanum tuberosum) plants with altered T6P levels specifically in their tubers were generated. Transgenic lines with elevated T6P levels (B33-TPS, expressing Escherichia coli osmoregulatory trehalose synthesis A [OtsA], which encodes a T6P synthase) displayed reduced starch content, decreased ATP contents, and increased respiration rate diagnostic for high metabolic activity. On the other hand, lines with significantly reduced T6P (B33-TPP, expressing E. coli OtsB, which encodes a T6P phosphatase) showed accumulation of soluble carbohydrates, hexose phosphates, and ATP, no change in starch when calculated on a fresh weight basis, and a strongly reduced tuber yield. [C-14] Glucose feeding to transgenic tubers indicated that carbon partitioning between starch and soluble carbohydrates was not altered. Transcriptional profiling of B33-TPP tubers revealed that target genes of SnRK1 were strongly up-regulated and that T6P inhibited potato tuber SnRK1 activity in vitro. Among the SnRK1 target genes in B33-TPP tubers, those involved in the promotion of cell proliferation and growth were down-regulated, while an inhibitor of cell cycle progression was up-regulated. T6P-accumulating tubers were strongly delayed in sprouting, while those with reduced T6P sprouted earlier than the wild type. Early sprouting of B33-TPP tubers correlated with a reduced abscisic acid content. Collectively, our data indicate that T6P plays an important role for potato tuber growth.